Effective treatment of vancomycin nephrotoxicity with continuous venous‐venous haemodiafiltration (CVVHDF) in a paediatric patient. (18th May 2020) - Lv, Meng; Ma, Shuli; Chen, Nan; Liu, Yan; Yu, Zutao
Abstract: What is known and objective: Vancomycin removal by dialysis uses methods that differ in type of dialysis membrane, dialysis fluxes and duration, ultrafiltration rate and Kt/Vurea (K = dialyser urea clearance, t = time on dialysis and V = total body water) in case of nephrotoxicity. We applied continuous venous‐venous haemodiafiltration (CVVHDF) to treat a paediatric case of vancomycin nephrotoxicity caused by high serum trough concentrations. Case summary: We report the case of a 4‐year and 7‐month‐old boy with serum trough concentration of vancomycin of 86.0 mg/L after a 2‐day treatment with vancomycin. His serum creatinine increased from 13.3 μmol/L at baseline to 227.0 μmol/L. We discontinued vancomycin and performed a 22‐hours CVVHDF with high‐flux membrane. Vancomycin decreased by 69.4% (82.1‐25.1 mg/L), and renal function improved. What is new and conclusion: Therapeutic drug monitoring and laboratory indicator measurements should be performed early during vancomycin treatment in paediatric patients with nephrotoxicity risk factors. Vancomycin removal by CVVHDF can be effective in paediatric acute kidney injury (AKI) associated with vancomycin‐associated nephrotoxicity (VAN). Abstract : Vancomycin‐associated nephrotoxicity is strongly associated with the high vancomycin serum trough concentrations. We described the dialysis treatment of a case of paediatric vancomycin nephrotoxicity with continuous venous–venous hemodiafiltration (CVVHDF), which was caused by high vancomycin serum trough concentrations associated with acute kidney injury. CVVHDF effectively removed vancomycin by 69.4% and improved renal function.